Redesigning the Bunaken National Park Collaborative Management Model to Actualize Sustainable Tourism Development - Elvira Mercy Katuuk; Titi Susilowati Prabawa; Noldy Tuerah (Eduvest - Journal of Universal Studies, 2024)
Bunaken National Park (BNP) was awarded the Global Winner and National Parks Category Winner in 2003 from the British Airways Tourism for Tomorrow Award for its success in implementing collaborative management (co-man). However, various recent studies actually show its ineffectiveness in managing BNP. The reasons are lack of quality conservation, the unfinished transformation of the profession of fishermen and farmers into the tourism industry, and the alienation of socio-cultural factors from the BNP management system. Using qualitative-descriptive research methods, this article aims to evaluate the implementation of the co-man model in BNP by analysing the role of actors (stakeholders) in order to actualize Sustainable Tourism Development (STD). The result is that actors have no significant role in implementing the co-man model due to the government’s dominance. This research also found goal disorientation in BNP management due to the ineffectiveness of the model. Its research questions are: how is the BNP co-man model effective in actualizing STD? What are the ideal roles of the actors and what basic prerequisites are needed for the collaboration model to operate effectively? This study urges the need for a multistakeholder approach by providing equal space for actors and placing STD as a "core business".